Gut microbiota dysbiosis and systemic inflammation in elderly Chinese hypertensive patients: a case-control study - Cheng, Yiwen; Huang, Yihua; Zhu, Zhangcheng; Ding, Wenwen; Liu, Xia; Xu, Xiaocui; Chen, Yangtian; Wang, Ling; Zhao, Longyou; Ling, Zongxin; Ye, Shiwei (Frontiers in Immunology, 2025)
Hypertension (HTN) remains the leading modifiable risk factor for global mortality and morbidity. The number of adults aged 30–79 with HTN has doubled worldwide, reaching approximately 1.3 billion, with nearly half unaware of their condition. Despite available therapies, the global control rate remains unacceptably low at around 20%, particularly in low- and middle-income countries. This substantial treatment gap contributes to a high burden of preventable cardiovascular events and strains healthcare systems globally, underscoring the urgent need for more effective, accessible, and personalized management strategies. Growing evidence suggests that gut microbiota dysbiosis plays a role in HTN pathogenesis, though its mechanistic basis remains incompletely understood. In this case-control study, we investigated the gut microbiota composition of 205 elderly Chinese individuals (153 HTN patients, 52 controls) using NovaSeq sequencing and assessed systemic inflammation using multiplex immunoassays. Enterotype analysis and receiver operating characteristic (ROC) modeling were employed to identify microbial signatures. HTN patients demonstrated significant β-diversity alterations and distinct taxonomic changes, characterized by enriched Escherichia_Shigella, Prevotella_9, and Enterococcus, and depletion of Blautia and butyrate-producing genera. The Escherichia_Shigella-dominated enterotype (E2) was significantly more prevalent in HTN. ROC-based biomarker analysis identified Blautia, Butyricicoccus, Lachnoclostridium, Prevotella_9, and Enterococcus as potential diagnostic biomarkers. HTN patients also exhibited elevated pro-inflammatory cytokines such as IL-1ra and TNF-α, indicative of chronic low-grade inflammation. Correlation analysis revealed strong associations between pathobionts (e.g., Escherichia_Shigella) and pro-inflammatory cytokines, and between butyrate producers (Blautia) and anti-inflammatory mediators. These findings underscore gut dysbiosis and systemic inflammation as key pathophysiological features in elderly hypertension and provide a foundation for developing microbiota-based diagnostic and therapeutic approaches for this population.